Penggambaran Dunia dalam The Naked Traveler 1 Year Round-The-World Trip Karya Trinity - Rudi Ekasiswanto (SEMIOTIKA: Jurnal Ilmu Sastra dan Linguistik, 2017)
This study is aimed at discussing The Naked Traveler 1 Year Round-The World Trip written by Trinity using literary theory about travelling proposed by Carl Thompson. The goal is to get more obvious depiction about the world as described by the author. This research uses qualitative method with descriptive data in forms of written and spoken words by subjects observed alongwith their observable behaviour. This research also uses analytic descriptive method by describing facts observed and followed by analysis. Analysis is conducted through sufficient elaboration and explanation. The result shows that The Naked Traveler 1 Year Round-The World Trip contains Trinity’s daily notes when travelling in Southern American countries. His writing contains elements of adventure by direct observation to the life of society in 9 countries: Brazil, Chille, Peru, Equador, Colombia, Cuba, Jamaica, Mexico and Guatemala, where he lives with local people and makes journey to world’s exotic tourism spots. Besides, the visited places are described in a subjective way, due to the close and near visibility having influence on the author. Keywords: local colour, Betawi, short stories anthology Terang Bulan Terang di Kali